A Note on the Making of Siliva the Zulu. (November 2022) - Hughes, Heather
Abstract: This note uncovers the role of John Langalibalele Dube in the making of Siliva the Zulu. Dube worked as an interpreter with Attilio Gatti and Harry Lugg of the Natal Native Affairs Department. The film's idealized version of Zulu traditional life well served their interests on the local political scene.